Conversations with Andre Dubus - Dubus, Andre, III, 1959- (Literary conversations series., 2013)
Over three decades, celebrated fiction writer Andre Dubus (1936-1999) published seven collections of short stories, two collections of essays, two collections of previously published stories, two novels, and a novella. While this is an impressive publishing record for any writer, for Dubus, who suffered a near-fatal accident mid-career, it is near miraculous. Just after midnight on July 23, 1986, after stopping to assist two stranded motorists, Dubus was struck by a car. His right leg was crushed and his left leg had to be amputated above the knee. After months of hospital stays and surgeri.